PENGARUH PERILAKU PERANGKAT DESA TERHADAP KECENDERUNGAN FRAUD DANA DESA (Studi Kasus Pada Desa Di Kecamatan Pulubala) - Lukfiah I. Radjak; Muhamad Taufik R Nani (JSAP : Journal Syariah and Accounting Public, 2020)
This research is aimed at finding the influence of the behavior of village apparatus on the tendency of village fund fraud in the Pulubala Subdistrict. The object of this research is the villages in the Pulubala Subdistrict. The sampling technique used in this study is the saturated sampling technique. The research data is the primary data obtained by distributing questionnaires to 77 respondents. The results of this study indicate that the behavior of village apparatus has a negative but significant effect on the tendency of village fund fraud with a significance level at 0.000. It shows that the better the behavior of the village apparatus, the lower the tendency for village fund fraud. The implication of the results of this study is the need to apply an ethical culture within the village government organizations by providing understanding to village apparatus that fraud is an unethical and immoral act that can not only harm oneself because it can lead to criminal corruption cases with the threat of imprisonment and tarnished reputation, but it can also cause wider harm, namely the losses to the state and society.